Intraocular Pressure and Estimated Cerebrospinal Fluid Pressure. The Beijing Eye Study 2011 - Wang, Ya Xing (Public Library of Science, 2014)
PURPOSE: To examine a potential association between intraocular pressure (IOP) and cerebrospinal fluid pressure (CSFP) in a population-based setting. METHODS: The population-based Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6±9.8 years (range: 50–93 years). A detailed ophthalmic examination was performed. Based on a previous study with lumbar cerebrospinal fluid pressure (CSFP) measurements, CSFP was calculated as CSFP [mm Hg] = 0.44×Body Mass Index [kg/m(2)]+0.16×Diastolic Blood Pressure [mm Hg]–0.18×Age [Years]. RESULTS: In multivariate analysis, IOP was associated with higher estimated CSFP (P<0.001; standardized correlation coefficient beta: 0.27; regression coefficient B: 0.20; 95% confidence interval (CI): 0.16, 0.24), after adjusting for thinner central corneal thickness (P<0.001; beta: 0.45; B: 0.04;95%CI: 0.04,0.04), smaller corneal curvature radius (P<0.001; beta:−0.11; B:−1.13;95%CI:−1.61,−0.64), shallower anterior chamber depth (P = 0.01; beta:−0.05; B:−0.33;95%CI:−0.59,−0.08) and longer axial length (P = 0.002; beta: 0.08; B: 0.20;95%CI: 0.08,0.32)), and after adjusting for the systemic parameters of higher pulse rate (P<0.001; beta: 0.08; B: 0.02;95%CI: 0.01,0.03), higher prevalence of arterial hypertension (P = 0.002; beta: 0.06; B: 0.32;95%CI: 0.12,0.53)), frequency of drinking alcohol (P = 0.02; beta: 0.04; B: 0.09;95%CI: 0.01,0.17), higher blood concentration of triglycerides (P = 0.001; beta: 0.06; B: 0.06;95%CI: 0.02,0.10) and cholesterol (P = 0.049; beta: 0.04; B: 0.08;95%CI: 0.00,0.17), and body mass index (P<0.001; beta:−0.13; B:−0.09;95%CI:−0.13,−0.06). In a parallel manner, estimated CSFP (mean: 10.8±3.7 mm Hg) was significantly associated with higher IOP (P<0.001; beta: 0.13; B: 0.18;95%CI: 0.13,0.23) after adjusting for rural region of habitation (P<0.001; beta:−0.37; B:−2.78;95%CI:−3.07,−2.48), higher systolic blood pressure (P<0.001; beta: 0.34; B: 0.06;95%CI: 0.05,0.07), higher pulse rate (P = 0.003; beta: 0.05; B: 0.02;95%CI: 0.01,0.03), taller body height (P<0.001; beta: 0.11; B: 0.05;95%CI: 0.03,0.07), higher blood concentration of cholesterol (P = 0.003; beta: 0.05; B: 0.17;95%CI: 0.06,0.28) and higher level of education (P = 0.003; beta: 0.09; B: 0.30;95%CI: 0.16,0.45). CONCLUSIONS: IOP was positively associated with estimated CSFP after adjusting for other ocular and systemic parameters. As a corollary, higher estimated CSFP was significantly associated with higher IOP in multivariate analysis. It fits with the notion that the arterial blood pressure, estimated CSFP and IOP are physiologically correlated with each other.